"Perpetually Self-Reflective": Lesbian Daughters of Mothers With Severe Mental Illness. (October 2015) - Carroll, Lynne; Tuason, Ma. Teresa G.
Twelve lesbians from various locales throughout the United States were interviewed regarding their experiences as sexual minorities and daughters of mothers with severe mental illness (SMI). Using resiliency and intersectionality as theoretical frameworks, and consensual qualitative research as methodology, we identified six domains: (a) childhood responses to mother's SMI, (b) childhood/adolescent coping with mother's SMI, (c) responses of others, (d) managing in adulthood, (e) coming out to self and others, and (f) relating sexual orientation to mother's SMI. Results show that all participants navigated adulthood by being "perpetually self-reflective." For many, dealing with their mothers' SMI gave them coping skills that made coming out much less challenging. For some, their mothers' SMI made it more difficult to come out to others. Participants discussed the complexly interwoven relation between these sources of marginalization, consistent with intersectionality theory.